Indonesian Stratigraphic Nomenclature revision: The first progress report - Herman Darman; Dwandari Ralanarko; Sugeng Sapto Surjono (Ikatan Ahli Geologi Indonesia, 2021)
A team was formed by the Indonesian Association of Geologist (IAGI) in early 2021 to revisit the Indonesian Stratigraphic Nomenclature which was issued in 1996. After 25 years many experts find that the document needs to be updated. The team is a mix of geologists with both academic and industry background. Several representatives from the Geological Agency who are involved in the Stratigraphic Lexicon document were also invited in the discussion. The team meeting was set on a regular basis to evaluate the existing nomenclature and look on areas for improvement. In each meeting the team will discuss a certain section of the nomenclature document. A three years work programme was set and reported on this article. In the first year the team will investigate areas for improvement, followed by revising necessary content in the second year. Implementation and promoting the nomenclature are planned for the third year.This short communication aims to engage a wider community on the process in revisiting the Indonesian Stratigraphic Nomenclature. Several examples of discussion topics in the meetings were included in this article. Readers will see potential areas for improvement and the team are open for suggestions.